2017
DOI: 10.1007/s10709-017-9957-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure of the zombi pea (Vigna vexillata (L.) A. Rich) gene pool based on SSR marker analysis

Abstract: Zombi pea (Vigna vexillata (L.) A. Rich) is an underutilized legume species and a useful gene source for resistance to biotic and abiotic stresses, although there is little understanding on its genetic diversity and structure. In this study, 422 (408 wild and 14 cultivated) accessions of zombi pea from diverse origins (201 from Africa, 126 from America, 85 from Australia, 5 from Asia and 5 from unknown origin) were analyzed with 20 simple sequence repeat (SSR) markers to determine its genetic diversity and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 34 publications
0
29
2
Order By: Relevance
“…In addition to environmental factors, genetic relatedness of the parents appeared to affect the successful hybridization of between different forms of zombi pea. In our study, the wild zombi pea (JP235863 from India) and the Bali cultivated zombi pea were genetically closely related [4], while in the study of Damayanti et al [8] the wild zombi pea used were from Africa and Australia in which they were genetically highly differentiated from the Bali cultivated zombi pea [4].…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…In addition to environmental factors, genetic relatedness of the parents appeared to affect the successful hybridization of between different forms of zombi pea. In our study, the wild zombi pea (JP235863 from India) and the Bali cultivated zombi pea were genetically closely related [4], while in the study of Damayanti et al [8] the wild zombi pea used were from Africa and Australia in which they were genetically highly differentiated from the Bali cultivated zombi pea [4].…”
Section: Discussionmentioning
confidence: 73%
“…The low polymorphism of SSR markers was also observed in the mapping parents of V. vexillata used by Marubodee et al [33] in which only 6.2% of 1,336 SSR markers were polymorphic. In addition, Dachapak et al [4] reported that only 21.2% of 1,024 SSR markers screened in 6 accessions of V. vexillata from Asia, Africa, Australia and America were polymorphic. However, the percentage of amplifiable SSR markers in Marubodee et al [33] and Dachapak et al [4] (65.4% and 58.1%, respectively) was higher than in our study (36.6%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations